Scaled conductance quantization unravels the switching mechanism in organic ternary resistive memories. Issue 9 (21st February 2020) - Cheng, Xue-Feng; Zhao, Yao; Ye, Wen; Yu, Chuang; He, Jing-Hui; Wang, Fu-Yi; Lu, Jian-Mei
Abstract : Scaled conductance quantization phenomenon was observed in organic ternary memory. A new perspective to understand the nature of resistance switching in organic ternary memory devices was provided. Abstract : Organic ternary resistive random access memories (RRAMs) can dramatically increase information density, but the effective device yield remains too low for practical applications. Further improvements are inefficient as the switching mechanism is poorly understood. Here, we demonstrate for the first time that quantized conduction occurs and is involved in the switching mechanism of organic ternary RRAMs. The conductance values in organic ternary RRAMs are quantified in units of the quantum conductance G 0 but scaled by a factor β, in contrast to that of inorganic RRAMs without scaling. In situ elemental mapping reveals that evaporated Al diffuses into organic layers and causes the formation of quantum channels. The organic materials act as diodes to regulate the external voltage and contribute to β ≪ 1. A roughly positive correlation between the scale factor β and ternary device yield was found, which might provide a new way to improve the ternary device yield and will stimulate more material innovation for organic ternary RRAMs.